The Transformational Capability of Tourism to Promote Women's Empowerment through Entrepreneurship - Xaxa, Augustin; Tiwari, Anju (Integrated Journal for Research in Arts and Humanities, 2023)
The tourist industry has a position of utmost significance within the economic context. The primary objective of this study is to investigate the many dimensions of tourism as a driver for active participation among a wide range of stakeholders in the field of tourist firms. This phenomenon possesses an inherent capacity to instigate and facilitate such engagement, both directly and indirectly. This research aims to illuminate the transformational capacity of tourism in promoting cooperation and involvement among stakeholders by analyzing the many aspects of this phenomenon. The major objective of this study is to emphasize the significant significance of promoting women's empowerment in the field of travel and tourism through entrepreneurial activity. This study utilizes the conceptual paradigm referred to as the 'Doors, Locks and the Key' to conduct a critical analysis and evaluation of the positive impacts of tourism in the Indian subcontinent. This study aims to explore the various methodologies, establishment processes, and progression strategies employed for women's empowerment in the tourism sector. Additionally, it seeks to analyze the implications of these efforts on the overall advancement of society. This present discourse aims to elucidate a proposed methodology for fostering entrepreneurial development in both rural and urban areas, with a specific focus on the field of tourism ventures. The central focus of the proposed methodology centers around the implementation of a carefully crafted growth strategy, customized to cater to the distinct requirements and ambitions of the aforementioned individuals residing in the designated area. This paper offers a series of recommendations pertaining to the prospective growth of entrepreneurial endeavors within the field of tourism and travel.